2020
DOI: 10.1159/000505822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anterior Kidney Calyx Involvement of Complex Stones on Outcomes for Patients Undergoing Percutaneous Nephrolithotomy

Abstract: Introduction: A number of factors that can impact the outcomes of percutaneous nephrolithotomy (PCNL) procedures have previously been investigated. Complex stones that extend to the anterior calyx could affect the success and complication rates of PCNL. Objective: We analyzed the effect of anterior calyx involvement on the outcomes of patients with complex stones treated with PCNL. Methods: A total of 132 consecutive patients who underwent PCNL due to complex stones (multiple, partial staghorn, or staghorn sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Meanwhile, the study results of Perepanova et al 15 suggested that excessive injury to renal parenchyma would increase the occurrence of postoperative systemic infection syndrome and urinary sepsis. It was considered in the study of Kalkanli et al 16 that complex calculi are more challenging than those confined to the renal pelvis, and lower red blood cell counts and higher infections after surgery are caused by a larger range of nephroscope swings during surgery. Despite being able to increase the calculus clearance rate, to a certain extent, via the establishment of multiple channels intraoperatively to compensate for the blind area of the main channel visual field, the injury to the kidneys can also be increased.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…Meanwhile, the study results of Perepanova et al 15 suggested that excessive injury to renal parenchyma would increase the occurrence of postoperative systemic infection syndrome and urinary sepsis. It was considered in the study of Kalkanli et al 16 that complex calculi are more challenging than those confined to the renal pelvis, and lower red blood cell counts and higher infections after surgery are caused by a larger range of nephroscope swings during surgery. Despite being able to increase the calculus clearance rate, to a certain extent, via the establishment of multiple channels intraoperatively to compensate for the blind area of the main channel visual field, the injury to the kidneys can also be increased.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…We have read the recently published article by Kalkanli et al [1] with great interest. It is an interesting study on a field that has been rarely studied in the literature.…”
mentioning
confidence: 99%
“…The study by Kalkanli et al [1] would have been more informative if the authors had presented data on the localization of the residual fragments. With the given results, we only understand that SFRs are higher in patients with anterior calyx stones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons who frequently performed percutaneous nephrolithotomy (PCNL) may have experienced the difficulty of reaching anterior calyx stones. However, there are not enough studies on this subject in the literature [2-4]. We aimed to be a preliminary work in this matter with this study.…”
mentioning
confidence: 99%